Immigration policy and immigrants' sleep: Evidence from DACA - Osea Giuntella; Jakub Lonsky; Fabrizio Mazzonna; Luca Stella (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
Stress is associated with sleep problems and poor sleep is linked to mental health and depression symptoms. The stress associated with immigrant status and immigration policy can directly affect mental health. While previous studies have documented the significant relationship between immigration policy and the physical and mental health of immigrants, we know little about the effects of immigration policy on immigrants' sleep patterns. Exploiting the approval of the Deferred Action for Childhood Arrivals (DACA) program in 2012, we study how immigrants' sleep behavior responds to a change in immigration policy. Consistent with the findings of previous research documenting the positive effects of DACA on mental health, we find evidence of a significant improvement in immigrants' sleep in response to this policy change. However, the estimated effects of the policy disappear rapidly after 2016. While temporary authorization programs such as DACA may have beneficial impacts on immigrants' sleep in the short term, the effects of such temporary programs can be rapidly undermined by uncertainty about their future. Thus, permanent legalization programs may be more effective at achieving long-term effects, thereby eliminating uncertainty around the legal status of undocumented immigrants.
Keywords: J15; I10; 330; Immigration; Sleep; Mental health; DACA